Scientific publications by teachers making up the jury examining students' theses at a peruvian medical school [Publicación científica de docentes que conforman el jurado dictaminador de tesis en una facultad de ciencias de la salud peruana] - Mamani-Benito, Oscar (2019)
ABSTRACT In view of the challenge posed by health scientific production in Peru and the limited number of publications contributed by teachers and students as of the undergraduate level, it was decided to determine the frequency of publication of scientific papers written by teachers making up the jury examining students' theses at the medical school of a private Peruvian university. To achieve this aim, a cross-sectional observational descriptive study was conducted of a population of 131 teachers who had evaluated theses accepted in the period 2015-2018. The search for papers was carried out in Google Scholar and the database Scopus. It was found that only 17.6% of the teachers had ever published some scientific work, of whom 9.2% had done so in the last five years. Additionally, only 6.9% had publications indexed in Scopus, and three had been certified as researchers by the National Council for Science, Technology and Technological Innovation of Peru. It was concluded that the publication rate by teachers evaluating theses at a Peruvian medical school is low and worrisome.